Numerical analysis of tsunami-triggered oil spill fires from petrochemical industrial complexes in Osaka Bay, Japan, for thermal radiation hazard assessment. (January 2020) - Nishino, Tomoaki; Takagi, Youhei
Abstract: This study assesses thermal radiation hazards from tsunami-triggered oil spill fires from petrochemical industrial complexes in Japan, and demonstrates that the assessment provides useful results for understanding how large an area will be exposed to high thermal radiation, and which tsunami vertical evacuation buildings will be in danger from the fires. A tsunami-triggered oil spill fire spread model was applied for the Port of Osaka, which has approximately 360 ha of petrochemical industrial complexes. A tsunami following a hypothetical magnitude 8.6 earthquake along the Nankai Trough subduction zone was considered. Oil spills caused by the tsunami and fire spread over oil were numerically simulated for several scenarios by varying the initial ignition location and time. Hazard maps representing the spatial distribution of maximum radiant heat flux from the fires were created. The calculations showed that one tsunami vertical evacuation building was exposed to a radiant heat flux of 40 kW/m 2 or more in the worst-case scenario. Therefore, this building is likely to be ignited by the fires, and it is recommended that this building be used as little as possible for tsunami vertical evacuation. In addition, ten tsunami vertical evacuation buildings, which are not likely to be ignited, would, in several scenarios, be exposed to a radiant heat flux that exceeds the minimum heat flux that causes human skin burns. Therefore, when rooftops of these buildings are used for refuge areas, measures for shielding these areas from thermal radiation need to be implemented, such as mounting parapet walls on rooftops.